Development and In Vitro Evaluation of Biocompatible PLA-Based Trilayer Nanofibrous Membranes for the Delivery of Nanoceria: A Novel Approach for Diabetic Wound Healing - GÜNDÜZ, OĞUZHAN (MDPI, 2021)
The attempts to explore and optimize the efficiency of diabetic wound healing's promotors are still in progress. Incorporation of cerium oxide nanoparticles (nCeO(2)) in appropriate nanofibers (NFs) can prolong and maximize their promoting effect for the healing of diabetic wounds, through their sustained releases, as well as the nanofibers role in mimicking of the extra cellular matrix (ECM). The as-prepared nCeO(2) were analyzed by using UV-Vis spectroscopy, XRD, SEM-EDX, TEM and FTIR, where TEM and SEM images of both aqueous suspension and powder showed spherical/ovoid-shaped particles. Biodegradable trilayer NFs with cytobiocompatibility were developed to sandwich nCeO(2) in PVA NFs as a middle layer where PLA NFs were electrospun as outer bilayer. The nCeO(2)-loaded trilayer NFs were characterized by SEM, XRD, FTIR and DSC. A two-stage release behavior was observed when the nanoceria was released from the trilayer-based nanofibers; an initial burst release took place, and then it was followed by a sustained release pattern. The mouse embryo fibroblasts, i.e., 3T3 cells, were seeded over the nCeO(2)-loaded NFs mats to investigate their cyto-biocompatibility. The presence and sustained release of nCeO(2) efficiently enhance the adhesion, growth and proliferation of the fibroblasts' populations. Moreover, the incorporation of nCeO(2) with a higher amount into the designed trilayer NFs demonstrated a significant improvement in morphological, mechanical, thermal and cyto-biocompatibility properties than lower doses. Overall, the obtained results suggest that designated trilayer nanofibrous membranes would offer a specific approach for the treatment of diabetic wounds through an effective controlled release of nCeO(2).
Keywords: nanoceria; PVA; PLA-based trilayer nanofibrous membranes; fibroblasts; diabetic wound healing; CERIUM OXIDE NANOPARTICLES; ELECTROSPUN NANOFIBERS; RELEASE; FIBROBLASTS; FABRICATION; DEPOSITION; PROTECTION; DRESSINGS; BEHAVIOR; ALCOHOL)